Clustering of loci controlling species differences in male chemical bouquets of sympatric Heliconius butterflies - Byers, Kelsey J. R. P. (Ecol Evol, 2020)
The degree to which loci promoting reproductive isolation cluster in the genome—that is, the genetic architecture of reproductive isolation—can influence the tempo and mode of speciation. Tight linkage between these loci can facilitate speciation in the face of gene flow. Pheromones play a role in reproductive isolation in many Lepidoptera species, and the role of endogenously produced compounds as secondary metabolites decreases the likelihood of pleiotropy associated with many barrier loci. Heliconius butterflies use male sex pheromones to both court females (aphrodisiac wing pheromones) and ward off male courtship (male‐transferred antiaphrodisiac genital pheromones), and it is likely that these compounds play a role in reproductive isolation between Heliconius species. Using a set of backcross hybrids between H. melpomene and H. cydno, we investigated the genetic architecture of putative male pheromone compound production. We found a set of 40 significant quantitative trait loci (QTL) representing 33 potential pheromone compounds. QTL clustered significantly on two chromosomes, chromosome 8 for genital compounds and chromosome 20 for wing compounds, and chromosome 20 was enriched for potential pheromone biosynthesis genes. There was minimal overlap between pheromone QTL and known QTL for mate choice and color pattern. Nonetheless, we did detect linkage between a QTL for wing androconial area and optix, a color pattern locus known to play a role in reproductive isolation in these species. This tight clustering of putative pheromone loci might contribute to coincident reproductive isolating barriers, facilitating speciation despite ongoing gene flow.